Flames of Justice in the Virtual Garden: A Preliminary Analysis of Tweets around the Death of an Indian Celebrity. Issue 1 (13th October 2021) - Sengupta, Subhasree; Tacheva, Jasmina
Abstract: Social media, particularly Twitter, is a powerful medium for expression and discussion across regions and communities in the world today. Using hashtags, a powerful and popular affordance of Twitter, several forms of civic engagement and online social campaigns emerge and inform public discourse. Although several prior studies have investigated the rhetorical impact of such narrative movements on Twitter, an important consideration lies in understanding the structural forms that such narratives take depending on the context and regional culture where the movement originates. To this end, this study embarks on a preliminary analysis of 150 tweets related to calls of action and social justice in the aftermath of the death of a popular Indian movie star. The analysis reveals a diverse spectrum of themes ranging from expressions of loss and grief to critiques of institutions and mechanisms of power. Parallel but powerful themes also demonstrate attempts to nurture and embolden the campaign. The aim of this analysis is to provide insights into how such channels of discourse might be designed to create a medium of freedom of expression and foster safe spaces for civic engagement.